El capital financiero de Rudolf Hilferding y la crisis contemporánea capitalista - Rojas Silva, Oscar David (2020)
This article explores the most interesting elements of the work of Rudolf Hilferding as a crucial link for the update of Marx’s analysis in his book Capital, in order to observe the phenomenon of the financial crisis in the 21st century. The capitalist mode of production has had great changes in the productive sphere but also in the relations of distribution expressed in the form of property. The joint-stock company breaks into the economic scene by destroying the traditional scheme of capitalism based on free competition and isolated private units. This leads us to the present where the great oligopolies have finished building the world market. Hilferding offers us the category of financial capital as a support to connect different levels of abstraction in Capital reaching its mature evolution. Without this methodological reflection the theory of the crisis falls under the economism of profit. By adding a theory of historical transition we put the phenomenon of the crisis in its historical context and not as an apocalyptic debacle. The economic-social formation requires pointing towards reflection on the subject that will have to act the political changes in the public arena. JEL: B14, B17, F54, G01